Nazm al-Qur’an: Islahi’s Methodology and Its Implications for Tafsir - Mukhtar, Mukhtar; Rahman; Pane, Ismail; Hadi, Henrizal; Usman, Usman; Zakaria, Gamal Abdul Nasir (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2024)
This research examines Amin Ahsan Iṣlāḥī's Tafsir: Selections from the Tadabbur al-Qur'an, which emphasizes the virtues of nazm (coherence) in the Qur'an. Iṣlāḥī's work provides deep insights into how the Qur'an is not merely a collection of isolated verses but rather a structured system with intricate relationships between verses, chapters, and the meanings they convey. The primary aim of this research is to explore how the Qur'an can be understood as an interconnected whole, where each part complements and reinforces the intended message. The research employs a qualitative library research method, utilizing written texts—primarily Selections from the Tadabbur al-Qur'an in English—as well as supplementary sources such as thesis, dissertations, books, and relevant academic journals. The findings of this research indicate that the Qur'an can be viewed as a cohesive system, where its verses and chapters are intricately linked, forming an inseparable unity. This research seeks to offer a novel perspective by underscoring the importance of understanding the nazm al-Qur'an, an aspect often overlooked in conventional tafsir. By incorporating data in the form of sentences, diagrams, and illustrations, this research aspires to provide a fresh understanding of the interconnections within the Qur'an, ultimately enriching our appreciation of this divine revelation. خلاصة تبحث هذه الدراسة في كتاب ”مختارات من تفسير تدبر القرآن“ لأمين أحسن إصلاحي، الذي يسلط الضوء على فضل الترابط في القرآن الكريم. ويقدم هذا النص نظرة عميقة في كيف أن القرآن ليس مجرد مجموعة من الآيات المتفرقة، بل هو نظام محكم له علاقات وثيقة بين الآيات والسور والمعاني الواردة فيه. إن التركيز الرئيسي لهذا البحث هو الكشف عن الكيفية التي يمكن من خلالها فهم القرآن كوحدة لا تتجزأ، حيث يترابط كل جزء منها ويعزز المعنى المراد إيصاله. والمنهج المتبع في هذا البحث هو البحث المكتبي ذو المنهج الكيفي، حيث إن البيانات المستخدمة هي النصوص المكتوبة وخاصة المختارات من تدبر القرآن المكتوبة باللغة الإنجليزية، بالإضافة إلى المصادر الأخرى الداعمة مثل الرسائل والأطروحات والرسائل الجامعية والرسائل العلمية والكتب والمجلات ذات الصلة. وتظهر نتائج هذه الدراسة أن القرآن ينظر إليه كنظام بمعنى أن أجزاء القرآن سواء كانت آيات أو حروفاً لها علاقة مع بعضها البعض باعتبارها كلاً لا يتجزأ. ويحاول هذا البحث تقديم الجديد من خلال تسليط الضوء على أهمية فهم نظم القرآن الذي كثيراً ما أهمل في التفسير التقليدي. ومن المتوقع أن يقدم هذا البحث فهماً جديداً للعلاقة بين أجزاء القرآن الكريم من خلال استخدام بيانات في شكل جمل ومخططات وصور، وكيف أن ذلك يثري فهمنا لهذا الوحي الإلهي. Abstrak Penelitian ini mengkaji Naskah Kitab Tafsir Selections From The Tadabbur al-Qur’an karya Amin Ahsan Iṣlāḥī yang menyoroti keutamaan nazm (koherensi) dalam al-Qur’an. Naskah ini memberikan wawasan mendalam tentang bagaimana al-Qur’an bukan hanya sekadar kumpulan ayat-ayat yang terpisah, melainkan sebuah sistem yang terstruktur dengan hubungan yang erat antara ayat, surah, dan makna yang terkandung di dalamnya. Fokus utama dari penelitian ini adalah untuk mengungkap bagaimana al-Qur’an dapat dipahami sebagai suatu kesatuan yang tidak terpisahkan, di mana setiap bagian saling terkait dan memperkuat makna yang ingin disampaikan. Metode yang digunakan dalam penelitian ini adalah penelitian kepustakaan (library research) dengan pendekatan kualitatif, di mana data yang digunakan adalah naskah tertulis, khususnya Selections From The Tadabbur al-Qur’an yang ditulis dalam bahasa Inggris, serta sumber-sumber pendukung lainnya seperti skripsi, tesis, disertasi, buku, dan jurnal yang relevan. Hasil penelitian ini menunjukkan bahwa al-Qur’an dipandang sebagai satu sistem dalam arti bagian-bagian dari al-Qur’an baik ayat atau pun surah, satu sama lain mempunyai hubungan sebagai satu kesatuan yang tak terpisahkan. Penelitian ini berusaha memperkenalkan kebaruan dengan menyoroti pentingnya pemahaman terhadap nazm al-Qur’an, yang selama ini sering terabaikan dalam tafsir konvensional. Dengan menggunakan data dalam bentuk kalimat, skema, dan gambar, penelitian ini diharapkan dapat memberikan pemahaman baru tentang hubungan antar bagian dalam al-Qur’an dan bagaimana hal ini memperkaya pemahaman kita terhadap wahyu Ilahi ini.